KENYAMANAN DAN PRODUKTIVITAS KERJA PEMAKAIAN RANCANGAN KURSI ERGONOMIS UNTUK PENJAHIT - Ahmad, Ahmad (Industrial and Systems Engineering Assessment Journal (INASEA), 2004)
This Article explains the outputs of the chair prototype research and do not explains the process of the chair design. Based on the obtained data, further is performed design of a chair and make its prototype. The result of the examination to some respondents during 60 minutes shows that sewing in the old chair average 116 pulses/minute, while using the new one is 104 pulses/minute. The frequency of sitting position change decreases from 13 times in the old chair to be 5 times in the new one. The questionnaire shows that using the new design gives better conformity than the old one. In this case, it can be concluded that sewing in the new design chair gives better conformity and increases the production comparing with using the old one.Â Â Â